Translational and Clinical Applications of Dental Stem Cell-Derived Exosomes - Mai, Zizhao; Chen, Huan; Ye, Yu; Hu, Ziyu; Sun, Wenjuan; Cui, Li; Zhao, Xinyuan (Frontiers in genetics, 2021)
Mesenchymal stem cells (MSCs) are promising seed cells in tissue repair and regeneration due to their featured properties of self-renewal and multipotency. However, a growing body of evidence has demonstrated that MSCs exert biological functions mainly through secreting exosomes. Exosomes, which contain RNA, proteins, lipids, and metabolites, are new players in regulating many fundamental processes and play important roles in regenerative medicine. Exosomes not only mimic the effects of their parent cells but also possess many advantages such as high drug loading capacity, low immunogenicity, excellent biocompatibility, and low side effects. Currently, a total of 6 different dental stem cells (DSCs) including dental pulp stem cells (DPSCs), stem cells from exfoliated deciduous teeth (SHEDs), periodontal ligament stem cells (PDLSCs), dental follicle progenitor cells (DFPCs), stem cells from apical papilla (SCAPs) and gingival mesenchymal stem cells (GMSCs) have been isolated and identified. DSC-derived exosomes (DSC-Exos) are actively involved in intercellular communication, anti-inflammation, osteogenesis, angiogenesis, immunomodulation, nurturing neurons, and promoting tumor cell apoptosis. In this review, we will critically review the emerging role and clinical application potential of DSC-Exos.